The Evolution of Legislation in the Field of Medically Assisted Reproduction and Embryo Stem Cell Research in European Union Members - Busardò, Francesco Paolo (Hindawi Publishing Corporation, 2014)
Medically Assisted Reproduction (MAR), involving in vitro fertilisation (IVF), and research on embryos have created expectation to many people affected by infertility; at the same time it has generated a surplus of laws and ethical and social debates. Undoubtedly, MAR represents a rather new medical field and constant developments in medicine and new opportunities continue to defy the attempt to respond to those questions. In this paper, the authors reviewed the current legislation in the 28 EU member states trying to evaluate the different legislation paths adopted over the last 15 years and highlighting those EU countries with no specific legislation in place and MAR is covered by a general health Law and those countries in which there are no laws in this field but only “guidelines.” The second aim of this work has been to compare MAR legislation and embryo research in EU countries, which derive from different origins ranging from an extremely prohibitive approach versus a liberal one, going through a cautious regulatory approach.